Atuação do psicólogo em contextos educacionais: a promoção à saúde na perspectiva do cuidado. - Ronchi, Juliana Peterle (2019)
The critical reflection on the psychologist’s performance in educational contexts highlights new forms of intervention and research focal points, in which, the fact of promoting health places itself as a possibility of work construction. The aim of this research is to understand the psychologist’s actions in an educational context, from the Health Promotion perspective. The following research is a qualitative case study, developed in a campus at Federal Institute of Education, Science and Technology (Ifes) in Espirito Santo state, using 12 (twelve) pre-selected intervention activities from the work register done by the psychology professional, in its first three years of working in the Institute, between 2012 and 2014. A observation guide was used as data collector on the selected documental material, based on the National Policy for Health Promotion (PNPS) from the Brazilian Ministry of Health: the intrasectoriality; intersectoriality; the importance towards the social, economic, political and cultural contexts from the institution as long as the subjects who participated in the intervention activities; the activities’ planning; attention, autonomy and caring towards the participants during the interventions; always considering their possible vulnerabilities. It was also taken into consideration, the name of the activity; its duration; who organized it besides the psychologist; its objectives; the theory, techniques and material used; and if any individual intervention took place. Three judges took part in this work, categorizing the documental material. For the data analysis, it was used the Content Analysis technique, and the Minitab 18 software for Fleiss’Kappa (k) and the independence Chi-squared test. The findings show that understanding the work of a psychologist in a educational context such as Ifes from the perspective of Health Promotion allows one to defend a caretaking perspective of work, consolidating critical practices, breaking the individualizing models, thus allowing this professional to question its own practices, building new acting forms that value autonomy, attention, caring, the institutional context, the environment and the diversity of professionals working in it. Thus, Health Promotion could collaborate with the school psychologist as a tool, allowing reflection on the path and the direction of work from a caretaking perspective. Furthermore, it displays the importance of the comprehension of the psychologist’s technical and theoretical backgrounds when working in educational contexts, thus influencing the working proposal construction.